Introgressive hybridization between two non‐native apple snails in China: widespread hybridization and homogenization in egg morphology. Issue 12 (31st July 2020) - Yang, Qian‐Qian; He, Chao; Liu, Guang‐Fu; Yin, Chuan‐Lin; Xu, Yi‐Peng; Liu, Su‐Wen; Qiu, Jian‐Wen; Yu, Xiao‐Ping
Abstract: BACKGROUND: Apple snails from the genus Pomacea have spread widely in paddy fields and other wetlands of southern China since their introduction in the 1980s. Pomacea spp. are commonly identified using mitochondrial COI sequences. However, sequencing the nuclear elongation factor 1‐alpha (EF1α) gene revealed genetic introgression between field populations of P. canaliculata and P. maculata, which produce surviving hybrids in laboratory crossbreeding experiments. RESULTS: In this study, we sequenced 1054 EF1α clones to design specific primers and established a fast and accurate multiplex polymerase chain reaction (PCR) method for genotyping EF1α. Combined with genotyping P. canaliculata and P. maculata based on mitochondrial COI and nuclear EF1α, we revealed the genetic introgression patterns of 30 apple snail populations in China. Purebred and hybrid individuals of P. canaliculata were widely distributed, while pure maculata‐EF1α type was detected only in a few individuals identified as P. canaliculata based on COI sequences. Each egg clutch had one to three genetic patterns, indicating multiple paternity or segregation in the progeny of hybrids. The higher percentages of hybrids in both wild populations and progeny than the homozygotes indicated a potential heterosis in the apple snail populations. Additionally, egg size and clutch size of the apple snails became homogeneous among the non‐native populations exhibiting introgression hybridization. CONCLUSION: Our findings emphasize the value of apple snails as a model to study the mechanisms and impacts of introgressive hybridization on fitness traits. © 2020 Society of Chemical Industry Abstract : Introgressive hybridization has occurred widely in non‐native Pomacea populations in China. The distinguishing egg morphology between P. canaliculata and P. maculata have become homogenized among the introgressive populations.